Cyanolipids in Sapindaceous Seed Oils - Kumar, Dinesh; Hasan, S.Q. (Asian Journal of Chemistry, 2011)
A number of sapindaceous seed oils have been investigated with respect to their cyanolipid constituents. All but one of the oils have this new class of lipids in amounts 37 %. These cyanolipids are of four different types, but all consist of long-chain fatty acids esterfied with an unsaturated isoprenoid hydroxyl or with dihydroxynitrile. The large amount of C20-carbon fatty acids usually found in the oil indicate an appreciable cyanolipid content because such acids are preferentially incorporated in nitrile-containing fractions. The fatty acid composition of the cyanolipid component has also been compared with that of triglycerides. S. obavatus seed oil was shown to contain a diester having two fatty acid moieties esterified with 1-cyano-2- hydroxymethylprop-1-ene-3-ol.